Designing Kidney Health Educational Content on Instagram for the Productive Age Group - Azifah Nur Diyanah; Ditya Fajar Rizkizha (Journal of Interdisciplinary Social Sciences and Humanities, 2026)
Kidney disease often goes unnoticed in its early stages, especially among productive age groups. The lack of awareness highlights the need for accessible health education. Instagram, a widely used visual platform among users aged 20–45, offers great potential for delivering health information. This study aims to design kidney health education content for Instagram tailored to the characteristics of productive age users. The research uses a design-based research (DBR) method with a qualitative-descriptive approach based on literature review. The results are used to develop educational content in the form of carousels, infographics, and engaging visual styles. Medical information is based on reliable sources such as WHO, the Indonesian Ministry of Health, and PERNEFRI. This study indicates that a structured design approach can enhance the effectiveness of kidney health education on social media.